Understanding Bridging Sites and Accelerating Quantum Efficiency for Photocatalytic CO2 Reduction - Wang, Kangwang; Hu, Zhuofeng; Yu, Peifeng; Balu, Alina M.; Li, Kuan; Li, Longfu; Zeng, Lingyong; Zhang, Chao; Luque, Rafael; Yan, Kai; Luo, Huixia (Nano-Micro Letters, 2023)
We report a novel double-shelled nanoboxes photocatalyst architecture with tailored interfaces that accelerate quantum efficiency for photocatalytic CO2 reduction reaction (CO2RR) via Mo–S bridging bonds sites in Sv–In2S3@2H–MoTe2. The X-ray absorption near-edge structure shows that the formation of Sv–In2S3@2H–MoTe2 adjusts the coordination environment via interface engineering and forms Mo–S polarized sites at the interface. The interfacial dynamics and catalytic behavior are clearly revealed by ultrafast femtosecond transient absorption, time-resolved, and in situ diffuse reflectance–Infrared Fourier transform spectroscopy. A tunable electronic structure through steric interaction of Mo–S bridging bonds induces a 1.7-fold enhancement in Sv–In2S3@2H–MoTe2(5) photogenerated carrier concentration relative to pristine Sv–In2S3. Benefiting from lower carrier transport activation energy, an internal quantum efficiency of 94.01% at 380 nm was used for photocatalytic CO2RR. This study proposes a new strategy to design photocatalyst through bridging sites to adjust the selectivity of photocatalytic CO2RR. Highlights: 1 The S-vacancies result in the change of d-band electronic state of Mo. 2 An internal quantum efficiency of 94.01% at 380 nm for photocatalytic CO2 reduction reaction (CO2RR). 3 The Mo–S bridging bonds optimize adsorption energies and accelerate CO2RR kinetics.